Integrated strategies for biosurfactant production and scale-up: Advances in fermentation engineering and computational modelling - Alice Angel Solomon; Dhanya Vishnu (Results in Engineering)
Biosurfactants, amphiphilic compounds produced by microbes, are increasingly being sold as cleaner products in place of man-made surfactants due to their biodegradability, low toxicity, and process stability under hostile conditions. Though their application in most areas of environmental remediation, biomedicine, and food processing is enormous, industrial-scale production is marred by poor yield, production cost, and constraints on downstream processing. This review is a multidisciplinary summary of development in the manufacture of biosurfactants, with balanced emphasis on fermentation engineering and simulation computing. It is a critical survey of six most common fermentation techniques—batch, fed-batch, continuous, submerged, solid-state, and mixed-culture systems—commenting on their operational merits and demerits and scalability. Additionally, application of computational tools like Density Functional Theory (DFT), Molecular Dynamics (MD), and Machine Learning (ML) is discussed for their potential for optimizing molecular structure, predicting interfacial performance, and speeding strain and process design. The work also discusses industrial limitations such as bioreactor design, substrate expense, process monitoring, regulatory concerns, and environmental issues. Through the combination of microbial biotechnology with computer simulation and process optimization, this research has strategic implications for the overcoming of present limits and towards cost-effective, scalable, and eco-friendly biosurfactant production.